1973
DOI: 10.1042/bj1340407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of luteinizing hormone and adenosine 3′:5′-cyclic monophosphate on the metabolism of free and esterified cholesterol in mouse Leydig-cell tumours

Abstract: 1. Male C57B1/6J mice bearing Leydig-cell tumours known to synthesize steroids in response to luteinizing hormone (LH) were given intravenous injections of [1,2-(3)H]cholesterol (50-100muCi per animal). Single-cell suspensions were prepared from the tumours 5-9 days after the injection of [(3)H]cholesterol and were incubated at 37 degrees C in foetal calf serum supplemented with 50mm-Tris-HCl, pH7.4. At various times after the start of incubation cells were collected by filtration of portions of the suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Leydig cells (Samuels and Eik-Nes, 1968). Conversion of cholesterol esters into cholesterol takes place in lipid droplets which, then, is carried to mitochondria for conversion into 20-, 22R dyhydroxycholesterol and the removal of side chain here, results in the production of pregnenolone (Moyle et al, 1973). Rest of the steps of pregnenolone conversion into testosterone takes place in the smooth endoplasmic reticulum (Bun-Ichi, 1973;Shikita and Tamaoki, 1965).…”
Section: Testicular Steroids and Regulation Of Steroidogenesismentioning
confidence: 99%
“…Leydig cells (Samuels and Eik-Nes, 1968). Conversion of cholesterol esters into cholesterol takes place in lipid droplets which, then, is carried to mitochondria for conversion into 20-, 22R dyhydroxycholesterol and the removal of side chain here, results in the production of pregnenolone (Moyle et al, 1973). Rest of the steps of pregnenolone conversion into testosterone takes place in the smooth endoplasmic reticulum (Bun-Ichi, 1973;Shikita and Tamaoki, 1965).…”
Section: Testicular Steroids and Regulation Of Steroidogenesismentioning
confidence: 99%
“…Courot (1971) reported a 10-to 15-fold increase in LH during the prepubertal period in the lamb. Bartke (1971a) and others (Herbst, 1967;Behrman & Armstrong, 1969;Behrman, Armstrong & Greep, 1970;Behrman, Moudgal & Greep, 1971; Moyle, Jungas & Greep, 1973a) have postulated a direct rôle for LH in regu¬ lating cholesterol and cholesterol ester metabolism in the gonads of various species. While it is well established that cholesterol is the major precursor molecule in steroid biosynthesis (Strickland, Nayfeh & French, 1970) (Davis, Bridges & Coniglio, 1966;Oshima & Carpenter, 1968;Ichihara, 1969;Simmons, 1969;Bartke, 1971b (Davis et al, 1966;Oshima & Carpenter, 1968) have reported little or no change in these levels with maturation of rat testes.…”
Section: Introductionmentioning
confidence: 99%